Digital migration - Leurs, Koen (London : SAGE Publications Ltd, 2023)
In contemporary discussions on migration, digital technology is often seen as a 'smart' disruptive tool. Bringing efficiencies to management, and safety to migrants. But the reality is always more complex. This book is a comprehensive and impassioned account of the relationship between digital technology and migration. From 'top-down' governmental and corporate shaping of the migrant condition, to the 'bottom-up' of digital practices helping migrants connect, engage and resist. Taking an interdisciplinary approach, Digital Migration explores: (a) The power relations of digital infrastructures across migrant recruitment, transportation and communication; (b) Migrant connections and the use of digital devices, platforms and networks; (c) Dominant digital representations of migrants, and how they're resisted; (d) The affect and emotion of digital migration, from digital intimacy to transnational family life; (e) How histories of pre and early-digital migration help us situate and rethink contemporary research; and (f) The realities of researching digital migration, including interviews with leading international researchers. Critical yet hopeful, Koen Leurs opens up the unequal power relations at the heart of digital migration studies, challenging us to imagine more just alternatives. Koen Leurs is an Associate Professor in Gender, Media and Migration Studies at the Graduate Gender Program, Department of Media and Culture, Utrecht University, the Netherlands. All author royalties for this book will be donated to the Alarm Phone, a hotline for boatpeople in distress.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Emigration and immigration -- Technological innovations